The Uneven Burden of Risk: Post‐Flood Waste Management, Health Hazards, and Environmental Racism in Porto Alegre, Brazil - Julia de Freitas Sampaio; Farinaz Gholam Veisi; Jair Ortega Castaneda (Antipode, 2026)
ABSTRACT This article examines the floods of 2024 in Porto Alegre, Brazil, through the lens of post‐disaster waste governance. We understand that this crisis was not a logistical failure, but the predictable result of a slow disaster already underway. Public institutions had been incrementally and selectively defunded along racial and class lines for years, which left the city unable to respond equitably once it flooded. To analyze that, we draw on data obtained from the Municipal Department of Urban Cleaning under Brazil's Transparency Law, GIS mapping, and census data. The results suggest that temporary waste sites were disproportionately sited in low‐income neighborhoods with a higher percentage of Black residents. These same sites also remained operational longer than those in wealthier areas. Although racial capitalism explains why this unevenness followed those lines, that explanation on its own is not new. The article's contribution is to identify cleanup duration, how long solid waste remains after a flood, as the measure through which that unevenness becomes visible. It does this by putting discard studies into conversation with disaster studies, and by treating that duration as a trace of environmental racism.